PERLINDUNGAN HUKUM MEREK TERKENAL AQUA TERHADAP PELANGGARAN MEREKNYA SELAMA MASA PANDEMI COVID-19 - Tomi Khoyron Nasir (M. Ramadhana Alfaris, 2021)
In the era of the Covid-19 pandemic, the world of industrial trade experienced a decline in production sales one of which was Aqua products which were impacted by the marketing of their production where other products had carried out the act of passing off the Aqua famous brand so that there was a violation of the brand in the form of violations of public order. So a new regulation is needed to improve legal protection for the Aqua brand so that it can minimize violations that occur during this Covid-19 pandemic. The purpose of this research is to study the forms of violations of the Aqua famous brand during the Covid-19 pandemic and to find out legal protection of the Aqua brand during Covid-19 pandemic. The method used in this research is a normative judicial approach because of this legal research uses secondary data from primary and secondary legal materials. The results of this research state the newest brand regulations can contribute to solving the problem of brand infringement during Covid-19 pandemic.